Photocatalytic Degradation of Bismarck Brown G Using Irradiated ZnO in Aqueous Solutions - Falah H. Hussein; Ahmed F. Halbus; Hussein A. K. Hassan; Wisam A. K. Hussein (E-Journal of Chemistry)
In this study, a homemade photoreactor equipped with 125w/542 high pressure mercury lamp as a source for near-UV radiation, was used for photocatalytic degradation of aqueous solutions of Bismarck brown G, (C18H20N8Cl2),4-[5-(2,4-Diamino-5-methylphenyl)diazenyl-2-methylphenyl] diazenyl -6-methylbenzol-1,3-diamin using zinc oxide. The disappearance of the original colored reactant concentrations with irradiation time was monitored spectrophotometrically by comparison with unexposed controls. It is noticed that the photocatalytic degradation process was high at the beginning and then decreased with time following pseudo first-order kinetics according to the Langmuir–Hinshelwood model. The effects of zinc oxide mass, dye concentration and temperature on photocatalytic decolorization efficiency (P.D.E.) were studied. P.D.E. reached 95.76% for Bismarck brown G after 50 minutes of irradiation at 293.15 K P.D.E. was found to increase with increasing temperature and the activation energy of photocatalytic degradation was calculated and found to be equal to 32±1 kJ mol-1.